Rapid prototyping of biomaterials : principles and applications - Narayan, Roger; ScienceDirect eBooks (Oxford : Woodhead Publishing, 2014)
Rapid Prototyping of Biomaterials: Principles and Applications provides a comprehensive review of established and emerging rapid prototyping technologies (such as bioprinting) for medical applications. Rapid prototyping, also known as layer manufacturing, additive manufacturing, solid freeform fabrication, or 3D printing, can be used to create complex structures and devices for medical applications from solid, powder, or liquid precursors. Following a useful introduction, which provides an overview of the field, the book explores rapid prototyping of nanoscale biomaterials, biosensors, artificial organs, and prosthetic limbs. Further chapters consider the use of rapid prototyping technologies for the processing of viable cells, scaffolds, and tissues. With its distinguished editor and international team of renowned contributors, Rapid Prototyping of Biomaterials is a useful technical resource for scientists and researchers in the biomaterials and tissue regeneration industry, as well as in academia. Comprehensive review of established and emerging rapid prototyping technologies (such as bioprinting) for medical applicationsChapters explore rapid prototyping of nanoscale biomaterials, biosensors, artificial organs, and prosthetic limbsExamines the use of rapid prototyping technologies for the processing of viable cells, scaffolds, and tissues.
Introduction to rapid prototyping of biomaterials -- Freeform fabrication of nanobiomaterials using 3D printing -- Rapid prototyping techniques for the fabrication of biosensors -- Rapid prototyping technologies for tissue regeneration -- Rapid prototyping of complex tissues with laser assisted bioprinting (LAB) -- Scaffolding hydrogels for rapid prototyping based tissue engineering -- Bioprinting for constructing microvascular systems for organs -- Feasibility of 3D scaffolds for organs -- 3-D organ printing technologies for tissue engineering applications -- Rapid prototyping technology for bone regeneration -- Additive manufacturing of a prosthetic limb.
"ISSN 2049-9493 (online)"--Title page verso.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Biomedical materials; Rapid prototyping; HEALTH & FITNESS -- Holism; HEALTH & FITNESS -- Reference; MEDICAL -- Alternative Medicine; MEDICAL -- Atlases; MEDICAL -- Essays; MEDICAL -- Family & General Practice; MEDICAL -- Holistic Medicine; MEDICAL -- Osteopathy; Biomedical materials; Rapid prototyping; Biocompatible Materials; Computer-Aided Design; Electronic books